2011
DOI: 10.1590/s0102-695x2011005000145
|View full text |Cite
|
Sign up to set email alerts
|

Chalcones from Myracrodruon urundeuva are efficacious in guinea pig ovalbumin-induced allergic conjunctivitis

Abstract: Abstract:The objective of the study was to verify the effects of dimeric chalcones (urundeuvines A, B, and C) from Myracrodruon urundeuva Allemão, Anacardiaceae (a Brazilian anti-inflammatory species), on an allergic conjunctivitis model. Male guinea-pigs were sensitized with two intraperitoneal injections of ovalbumin (10 μg dissolved in 0.5 mL saline and emulsified in 0.5 mL Freund's adjuvant), at days 0 and 7. At day 24, the animals were submitted to an ocular instillation (right eyes) with ovalbumin. At th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 36 publications
(42 reference statements)
0
8
0
1
Order By: Relevance
“…In the shoot stems, the presence of urundeuvine A is observed, as described by Bandeira (2002), as well as a derivative of urundeuvine A. Chalcones represent a class of compounds with pronounced gastroprotective activity (Mota et al, 2009). Urundeuvines isolated from M. urundeuva have a pronounced antiulcerogenic effect, in addition to the anti-inflammatory, analgesic (Viana et al, 2003;Albuquerque et al, 2011;Rodrigues et al, 2002) and also neuroprotective effects (Calou et al, 2014;Nobre-Júnior et al, 2009). In the shoot leaves, the presence of gallotannins, such as tri-galloyl hexoside, tetragalloylglucose, penta galloyl-hexoside and hexagalloylhexoside was observed in the present study.…”
Section: Discussionmentioning
confidence: 72%
“…In the shoot stems, the presence of urundeuvine A is observed, as described by Bandeira (2002), as well as a derivative of urundeuvine A. Chalcones represent a class of compounds with pronounced gastroprotective activity (Mota et al, 2009). Urundeuvines isolated from M. urundeuva have a pronounced antiulcerogenic effect, in addition to the anti-inflammatory, analgesic (Viana et al, 2003;Albuquerque et al, 2011;Rodrigues et al, 2002) and also neuroprotective effects (Calou et al, 2014;Nobre-Júnior et al, 2009). In the shoot leaves, the presence of gallotannins, such as tri-galloyl hexoside, tetragalloylglucose, penta galloyl-hexoside and hexagalloylhexoside was observed in the present study.…”
Section: Discussionmentioning
confidence: 72%
“…Bernardes et al [62], using S. terebinthifolius extract, showed a reduction in the inflammatory process exacerbated in their studies and found antimycobacterial activity attributed to the flavonoids identified in this extract. Studies of the Myracrodruon urundeuva , also known in ethnopharmacology for its anti-inflammatory action, confirmed the presence of tannins and flavonoids in various parts of the plant [63,64].…”
Section: Resultsmentioning
confidence: 99%
“…Jandú et al (2013), Gomes et al (2013), and Sá et al (2009) demonstrated the antibacterial activity of "aroeira" against gram-positive and gram-negative bacteria, mainly by the composition of their secondary metabolites that mainly involve tannins, flavonoids, and alkaloids. Others (Albuquerque et al 2011) demonstrated that chalcones from M. urundeuva stem barks presented anti-inflammatory and antioxidant effects and drastically inhibited myeloperoxidase (inflammation marker) activity pointing them as potential candidates for the treatment of inflammatory conditions. In addition, an important neuroprotective property of a standardized extract (rich in tannins and chalcones) from M. urundeuva that was shown to be effective on a Parkinson's disease model in rats (Calou et al 2014).…”
Section: Resultsmentioning
confidence: 99%